2019
DOI: 10.1111/myc.13040
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of allele distribution in a hybrid population of the Cryptococcus neoformans species complex

Abstract: Summary Background The sister yeast species Cryptococcus neoformans (serotype A) and Cryptococcus deneoformans (serotype D) are causative agents of deadly cryptococcosis and fungal meningoencephalitis. These haploid yeasts can hybridise in nature, giving rise to AD hybrids that are predominantly diploid or aneuploid. Despite their increasing prevalence in clinical settings, much remains unknown about the allelic distribution patterns in AD hybrid strains. Objectives This study aims to characterise allele distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…The higher ploidy in hybrid progeny from bilateral msh2 Δ x msh2 Δ crosses was also associated with significantly more heterozygosity across their genomes than their counterparts from wild-type C. neoformans x C. deneoformans crosses. It is possible that this higher level of heterozygosity contributes to the increased viability by masking deleterious alleles or overcoming Bateson-Dobzhansky-Muller genetic incompatibilities, as has been observed in previous studies of C. neoformans x C. deneoformans hybrids [48,66].…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The higher ploidy in hybrid progeny from bilateral msh2 Δ x msh2 Δ crosses was also associated with significantly more heterozygosity across their genomes than their counterparts from wild-type C. neoformans x C. deneoformans crosses. It is possible that this higher level of heterozygosity contributes to the increased viability by masking deleterious alleles or overcoming Bateson-Dobzhansky-Muller genetic incompatibilities, as has been observed in previous studies of C. neoformans x C. deneoformans hybrids [48,66].…”
Section: Discussionmentioning
confidence: 82%
“…Several studies of C. neoformans x C. deneoformans hybrid genomes have utilized restriction fragment length polymorphism analysis or PCR with sequence-specific primers to assess their genomes. Through these methods it has been demonstrated that while C. neoformans x C. deneoformans hybrids are heterozygous at most loci, some chromosomes seem to be recombinant, indicative of potential mitotic or meiotic recombination [44,4648].…”
Section: Introductionmentioning
confidence: 99%
“…During sexual mating, the two parental nuclei have been observed to fuse at earlier stages of sexual development (e.g., in the zygote or hyphae), providing opportunities for mitotic recombination to facilitate LOH at certain chromosomal regions before meiosis. A recent analysis of 297 lab-derived AD hybrid progeny strains generated from a single cross revealed the hybrids to experience extensive loss of chromosomes [74]. Both partial and complete chromosome loss and duplication have been observed in some AD hybrids.…”
Section: Loss Of Heterozygositymentioning
confidence: 99%
“…Interestingly, natural AD hybrids show a preferential retention of specific alleles and chromosomes from one of the two parents, suggesting that those alleles may offer survival and growth benefits under specific conditions [68]. Allele distributions in the genomes of AD hybrids often show significant departures from Mendelian ratios with alleles of one parent preferred over that of the other at certain loci [74]. In fact, Samarasinghe et al [75] found genome-wide allele distribution in 297 AD hybrids to be significantly skewed in favor of the C. deneoformans parent from which the hybrids inherited mitochondria.…”
Section: Loss Of Heterozygositymentioning
confidence: 99%
“…Genomic plasticity is apparent in AD hybrids, but it is unclear which mechanisms are most important for adaptation. Most AD hybrids are close to diploid and, although they produce sexual spores, these appear to have been produced by an aberrant form of meiosis (Lengeler et al 2001;Sun and Xu 2007;Hu et al 2008;Samarasinghe et al 2020b). The two parental genomes are 85-90% divergent at the sequence level, and they are known to have karyotype differences (Kavanaugh et al 2006;Sun and Xu 2009).…”
Section: Introductionmentioning
confidence: 99%